2010
DOI: 10.1111/j.1553-2712.2010.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intranasal Fentanyl for the Relief of Pediatric Orthopedic Trauma Pain

Abstract: Objectives: The objective was to evaluate the use of a single 2 lg ⁄ kg dose of intranasal fentanyl as analgesia for painful orthopedic injuries in children presenting to a pediatric emergency department (ED).Methods: This was a prospective, nonblinded interventional trial, in a convenience sample of patients 3 to 18 years of age seen in a tertiary care pediatric ED. All had clinically suspected fractures and were treated between July and November 2006. Eligible patients had moderate to severe pain based on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 29 publications
(46 reference statements)
0
38
0
2
Order By: Relevance
“…19,40,41 A number of observational studies in prehospital and emergency department settings have evaluated the efficacy and safety of fentanyl and morphine. [29][30][31][32]42,43,44 These studies uniformly showed that fentanyl and morphine compare favorably to one another in both the reduction of pain and lack of adverse events. In 2006, Kanowitz et al conducted a retrospective chart review of 2,129 patients who were administered fentanyl in an out-of-hospital setting and concluded fentanyl was effective in decreasing pain scores without causing substantial hypotension, respiratory depression, hypoxia, or sedation.…”
Section: Safety and Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…19,40,41 A number of observational studies in prehospital and emergency department settings have evaluated the efficacy and safety of fentanyl and morphine. [29][30][31][32]42,43,44 These studies uniformly showed that fentanyl and morphine compare favorably to one another in both the reduction of pain and lack of adverse events. In 2006, Kanowitz et al conducted a retrospective chart review of 2,129 patients who were administered fentanyl in an out-of-hospital setting and concluded fentanyl was effective in decreasing pain scores without causing substantial hypotension, respiratory depression, hypoxia, or sedation.…”
Section: Safety and Efficacymentioning
confidence: 99%
“…The panel acknowledges the studies demonstrating the safety and efficacy of fentanyl at higher doses, but upon consideration of evidence felt that 1 μg/kg of fentanyl was the most reasonable starting point. 35,43 Future high quality studies are needed to further delineate the optimum dosing for both morphine and fentanyl.…”
Section: Safety and Efficacymentioning
confidence: 99%
“…As is evident in this study, pain rating scales were adequately tailored to pre-specified age groups, with younger children using the Face Pain Scale-Revised (FPS-R) and older children using the Visual Analog Scale (VAS), taking into consideration each age group's cognitive abilities, which confirms the appropriate utilization and strength of the methodology. The authors in this trial used an adequate dose of intranasal fentanyl of 1.5 µg/kg, as the average of 1-2 µg/kg, although some other trials had a higher dosing regimen (10,11). This dosage was comparable to that in the majority of studies conducted on intranasal fentanyl administered via atomization (4,(12)(13)(14)(15).…”
Section: Resultsmentioning
confidence: 73%
“…In our opinion, the results obtained from this study highlighted the higher profile of adverse events associated with ketamine than that with intranasal ketamine in comparison with intranasal fentanyl. Intranasal fentanyl has weidely been widely been used over the past years, and for quite some time now, and it has been proven by several studies to be a safe and effective me of analgesia with limited side effects (10,11,18).…”
Section: Resultsmentioning
confidence: 99%
“…(17) Yet another study showed that it provides effective analgesia for paediatric patients with painful orthopaedic traumas. (18) While the use of intranasal fentanyl in the ED has been shown to be effective in paediatric populations, (9) METHODS An open-label study was conducted to evaluate the effectiveness of the addition of 1.5 mcg/kg intranasal fentanyl to 2 mg/kg intravenous tramadol (fentanyl + tramadol arm, n = 10) as compared to the administration of 2 mg/kg intravenous tramadol alone (tramadol-only arm, n = 10) in adult patients with moderate to severe pain due to acute musculoskeletal injuries.…”
Section: Introductionmentioning
confidence: 99%